EFEKTIVITAS MODEL PROBLEM BASED INSTRUCTION TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SDN BOJONGRENGED 1 - Nurhayati Sholihah, Ismi (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
Science learning in elementary schools is still dominated by conventional methods that do not actively engage students, resulting in low learning outcomes. This issue is also found at SDN Bojongrenged 1, Tangerang Regency, where most fourth-grade students have not achieved the Minimum Mastery Criteria (KKM). This study aims to analyze the effect of the Problem Based Instruction (PBI) learning model on science learning outcomes, particularly on the topic of "types of energy and their transformations." The novelty of this research lies in the implementation of the PBI model in classrooms with limited space and minimal resources, a condition that is rarely the focus of previous studies. This study employed a quasi-experimental design with a nonrandomized control group pretest-posttest model, involving 43 students as a saturated sample. Data were collected using multiple-choice tests that had been validated and proven reliable, based on three cognitive indicators of Bloom’s taxonomy: knowledge (C1), comprehension (C2), and application (C3). The results showed a significant increase in the average score of the experimental class (from 46.05 to 87.27), compared to the control class (from 40.90 to 78.29). The paired sample t-test and independent sample t-test results showed significance values of 0.000 and 0.011 (p < 0.05), indicating that the PBI model had a significant effect on science learning outcomes.Thus, the PBI model has proven effective in improving students’ conceptual understanding of science in an active and contextual manner, and can serve as an alternative instructional strategy that adapts well to facility limitations in elementary schools. ABSTRAK Pembelajaran Ilmu Pengetahuan Alam (IPA) di sekolah dasar masih didominasi oleh metode konvensional yang kurang melibatkan siswa secara aktif, sehingga berdampak pada rendahnya hasil belajar. Hal ini juga terjadi di SDN Bojongrenged 1 Kabupaten Tangerang, di mana mayoritas siswa kelas IV belum mencapai Kriteria Ketuntasan Minimal (KKM). Penelitian ini bertujuan untuk menganalisis pengaruh model pembelajaran Problem Based Instruction (PBI) terhadap hasil belajar IPA pada topik "macam-macam energi dan perubahannya". Kebaruan penelitian terletak pada penerapan model PBI di ruang belajar terbatas dengan sumber daya minimal, kondisi yang jarang menjadi fokus penelitian sebelumnya. Penelitian ini menggunakan desain eksperimen semu dengan model nonrandomized control group pretest-posttest, melibatkan 43 siswa sebagai sampel jenuh. Data diperoleh melalui tes pilihan ganda yang telah divalidasi dan reliabel, berdasarkan tiga indikator kognitif taksonomi Bloom: pengetahuan (C1), pemahaman (C2), dan aplikasi (C3). Hasil menunjukkan peningkatan signifikan pada nilai rata-rata kelas eksperimen (dari 46,05 menjadi 87,27), dibandingkan kelas kontrol (dari 40,90 menjadi 78,29). Uji paired sample t-test dan independent sample t-test menunjukkan signifikansi masing-masing 0,000 dan 0,011 (p < 0,05), yang menandakan bahwa model PBI berpengaruh signifikan terhadap hasil belajar IPA. Dengan demikian, model PBI terbukti efektif dalam meningkatkan pemahaman konsep IPA secara aktif dan kontekstual, serta dapat menjadi alternatif strategi pembelajaran yang adaptif terhadap keterbatasan fasilitas di sekolah dasar.